Do Frequency of Visit and Length of Stay Alter Perceived Cognitive Destination Image? A Multivariate Approach - R., Sabari Shankar; Koshy, Elizabeth Renju; Chandan (Prabandhan: Indian Journal of Management, 2021)
The Indian tourism industry is competing with global destinations through effective and lucrative strategies. Strategic destination branding is one of the finest ways of achieving the frontier. This requires careful analysis of tourists’ perception and behavior from time to time and inculcate insights on the branding process. Accordingly, this research work is an extract from a major research that focused on whether the behavioral elements such as tourists’ frequency of visit and length of stay to/in the destination influenced the perceived cognitive destination image. Even though literary sources indicated the connection between these factors, a void was identified in terms of the aspects of the cognitive image, specifically in the Indian context. Hence, a district in Tamil Nadu that had high tourist attractions and potentialities to serve distinct tourist motives was chosen for the study. The respondents answered a structured questionnaire that contained the necessary questions and statements on tourists’ sociodemographic characteristics, frequency of visit, length of stay, and perception of the cognitive image of the destination. The sample size was rounded to 327 after data cleaning. Simple percentage analysis revealed that the highest percentage of tourists were frequent visitors and stayed in the destination for more than a week. This is a good sign for marketers to increase the tourists’ inflow and invest in branding strategies. The multivariate analysis of variance technique of SPSS was employed to analyze the data. The results indicated that despite the frequency of visit and length of stay, some of the cognitive belief aspects remained unaltered. Suggestions were made to the marketers on deploying the cognitive image aspects while designing the advertisement campaigns and including the cognitive image elements in the branding process. Theoretical implications were also indicated on the outcome of this research. Also, limitations were stated in terms of the sample size, research location, and other aspects. Scope for further research was also indicated.